The impact of "Maritime Silk Road" on trade between China and Obor countries : China’s container throughput forecast based on quantitative analysis - Xu, Junjie (2016)
Under “one belt one road” strategy, China and partner countries would have a spacious room for business cooperation. As the starting point of the maritime Silk Road, China plays a significant role in shipping trade in regards to both bulk trade and container trade. This article focuses on how China’s own economic situation would affects container throughput. By looking the past decades information, this article will produce a series factors ranging from macro-economic factors to micro business factors that affect container throughput. In the macro factors, this article adopts six elements to which belongs to two categories. Agriculture, manufacturing and service industry are three elements belongs to the GDP composition. While labor force, foreign direct investment and graduate students representing labor productivities, capital productivities and technology productivities respectively belongs to the drivers of GDP growth. In the micro factor experiment, this article collects general kinds of cargo based on the categories according to national bureau statistics of China. This article will adopt gray relational modelling methods and several series of data collected from year 2003 to 2014 to construct this model. This experiment results show service industry of China shares the most similar patterns with the gang of container throughput and export value of refined petrol products are the most influential cargo related to the overall China’s container throughput. This finding provides a basis for the prediction of future China’s container throughput when referring to China’s 13th five-year plan.